Associations between bullous pemphigoid and hematological diseases: Literature review on mechanistic connections and possible treatments - Yang, Yuyan; Zhao, Wenling; Yang, Nan; Cui, Shengnan; Jin, Hongzhong; Li, Li (Frontiers in Immunology, 2023)
Bullous pemphigoid is an autoimmune blistering disorder that primarily occurs in elderly patients. Reports indicate that BP coexists with various hematological diseases, including acquired hemophilia A, hypereosinophilic syndrome, aplastic anemia, autoimmune thrombocytopenia, and hematological malignancies. Early identification of these comorbidities contributes to a better control and reduced mortality. This article details the atypical clinical manifestations of BP when associated with hematological diseases, specific diagnostic strategies, underlying mechanistic connections, and possible treatments. Cross-reactivity between autoantibodies and exposed abnormal epitopes, shared cytokines and immune cells, together with genetic susceptibility are the most common connections between BP and hematological diseases. Patients were most often successfully treated with oral steroids combined with medications specifically targeting the hematological disorders. However, the individual comorbidities require specific considerations.